2017
DOI: 10.3389/fpls.2017.01207
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of 2,4-D or Dicamba with Glufosinate for Control of Glyphosate-Resistant Giant Ragweed (Ambrosia trifida L.) in Glufosinate-Resistant Maize (Zea mays L.)

Abstract: Glyphosate-resistant (GR) giant ragweed is a problematic broadleaf weed in crops including maize and soybean in the Midwestern United States. Commercialization of crops with 2,4-D or dicamba and glufosinate resistance will allow post-emergence (POST) applications of these herbicides. Therefore, information is needed on how 2,4-D/dicamba will interact with glufosinate in various rate combinations. The objectives of this study were to evaluate the interaction of glufosinate plus 2,4-D and/or dicamba for control … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 57 publications
1
20
1
Order By: Relevance
“…Likewise, Crow et al ( 2016 ) reported >87% control of >20 cm tall Palmer amaranth with dicamba plus diflufenzopyr applied alone or in tank-mixture with glyphosate, mesotrione, tembotrione, mesotrione plus rimsulfuron, or tembotrione plus thiencarbazone at 4 WAPOST. Nonetheless, the dependence on POST herbicides with a single site of action must be avoided to prevent the evolution of HR weeds (Chahal and Jhala, 2015 ; Chahal et al, 2017 ; Ganie and Jhala, 2017b ). Furthermore, the confirmation of GR Palmer amaranth in a GR soybean/maize production field in south-central Nebraska signifies that dependence on a single POST herbicide program is not a reliable option (Chahal et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Likewise, Crow et al ( 2016 ) reported >87% control of >20 cm tall Palmer amaranth with dicamba plus diflufenzopyr applied alone or in tank-mixture with glyphosate, mesotrione, tembotrione, mesotrione plus rimsulfuron, or tembotrione plus thiencarbazone at 4 WAPOST. Nonetheless, the dependence on POST herbicides with a single site of action must be avoided to prevent the evolution of HR weeds (Chahal and Jhala, 2015 ; Chahal et al, 2017 ; Ganie and Jhala, 2017b ). Furthermore, the confirmation of GR Palmer amaranth in a GR soybean/maize production field in south-central Nebraska signifies that dependence on a single POST herbicide program is not a reliable option (Chahal et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…More recently, GR Palmer amaranth has also been confirmed in Nebraska (Chahal et al, 2017 ). In view of the widespread occurrence of six GR broadleaf weeds in Nebraska, tank-mixing glyphosate with other site of action herbicides and rotation of GR maize with other HR crop traits has become important to diversify the number of herbicide options for management of HR weeds such as Palmer amaranth (Ganie et al, 2017 ; Ganie and Jhala, 2017b ).…”
Section: Introductionmentioning
confidence: 99%
“…The rapid resistance evolution to glyphosate highlights the relevance of implementing different weed management strategies (Ganie and Jhala, 2017). In general, the mixtures of the alternative herbicide with glyphosate showed additive effects, because synergistic interactions between agrochemicals are rare (Cedergreen, 2014), and it is more common to observe antagonistic effects of glyphosate mixed with herbicides, such as atrazine, cloransulam, dicamba, lactofen, and topramezone (Vidal et al, 2003;Harre et al, 2018).…”
Section: Chemical Control Of Glyphosate-resistant Populations Of Conymentioning
confidence: 99%
“…The herbicide combinations with different modes of action, either in sequential application or tank-mix, can contribute to improve the control of resistant weeds (Tornisielo et al, 2013), and additionally, may also avoid or delay evolution of resistance (Ganie and Jhala, 2017). Improvements in weed control have been observed in glyphosate-resistant species by applying glyphosate tank-mix combinations (Riley and Bradley, 2014), in some cases, the control was improved by 25-30% compared to glyphosate alone (Eubank et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The occurrence of bipyridylium resistance has led to an increase in the use of the herbicides glyphosate [5-enolpyruvylshikimate-3-phosphate synthase (EPSPS) inhibitor], glufosinate [glutamine synthetase (GS) inhibitor], 2,4-D (synthetic auxin), flazasulfuron [acetolactate synthase (ALS) inhibitor], and pyraflufen-ethyl [protoporphyrinogen oxidase (PPO) inhibitor] among others. Using numerous herbicides allows a broad herbicidal spectrum that includes activity against monocotyledonous and dicotyledonous weeds, and rapid onset of action and long persistence of some herbicides (Ganie and Jhala, 2017 ).…”
Section: Introductionmentioning
confidence: 99%